Performance evaluation of solar still using energy storage biomaterial with porous surface: An experimental study and environmental analysis. (April 2023) - Dhivagar, Ramasamy; Shoeibi, Shahin; Parsa, Seyed Masoud; Hoseinzadeh, Siamak; Kargarsharifabad, Hadi; Khiadani, Mehdi
Abstract: The use of energy storage material can have a significant influence on the water productivity of solar still. Water productivity by solar energy and without environmental pollution are the advantages of using solar desalination in addition to being cost-effective. In this study, a novel conch shell biomaterial was considered as an energy storage material and porous media in a solar still (CSSS) to improve the performance of the system. The conch shell biomaterial stores the thermal energy of the sun and releases it into the saline water when the solar radiation is low. Also, the porous surface of the conch shells acts like a porous absorber and absorbs a large amount of solar radiation which led to increasing the water temperature. The experiments were conducted in the climatic conditions of Ongole city (15.5057° N, 80.0499° E), India. The results showed that the cumulative productivity of solar still using conch shells as an energy storage biomaterial and porous media was achieved 10.8% better than conventional solar still (CSS). Moreover, the CSSS outperformed CSS in terms of energy and exergy efficiency by 10.3% and 9%, respectively. In addition, the CPL and CO2 emissions mitigation of modified solar still were enhanced by about 11.1% and 10.9% more than conventional ones. Graphical abstract: Image 1